Evaluasi Instalasi Pengolahan Air Babakan Pada Perumdam TKR Kabupaten Tangerang - Rizky Fathan Witjaksono; Mohamad Rangga Sururi (Fakultas Teknik, 2023)
Babakan Water treatment plant evaluation aims to meet the community needs for drinking water in Babakan, Tangerang Subdistrict. To meet the needs for drinking water, Perumdam Tirta Raharja in the Tangerang district has a water treatment plant with volumetric flow rate 80 L/second with the raw water source being the Cisadane River. This study refers to the design criteria based on the literature and evaluation of existing water treatment installations based on secondary data. The purpose of this study was to evaluate the performance of the Babakan WTP in terms of quality from the comparison of the test results of raw water sources and distribution with the applicable quality standards and quantity from the calculation of the discharge and the dimensions of the treatment unit. In the Babakan WTP PDAM TKR, optimization can be done by changing the flocculation unit value of detention time from 0.42 minutes to 15 minutes, and the value of the Relative Capacity of the Tube (C) from being changed from 72 m3 to 468.3 m3 so that the gradient value speed to 60 s -1. Solution of sedimentation unit is the design parameter that is not suitable is the surface loading rate less than the design criteria 60 m3/m2. days, to increase the value of the surface loading rate can be done to reduce the surface area of the tub. Settler velocities bigger than the design criteria may cause grinding of the settler surface and cause the flow to become turbulent. The solution for the filtration unit changed the dimensions by increasing the width of the filtration tank twice to 3 m.